Real-time simulation of shipboard power system and energy storage device management - Li, Dingyi (Kansas State University, 2014)
Many situations can cause a fault on a shipboard power system, especially in naval battleships. Batteries and ultra-capacitors are simulated to be backup energy storage devices (ESDs) to power the shipboard power system when an outage or damage occurs. Because ESDs have advantages such as guaranteed load leveling, good transient operation, and energy recovery during braking operation, they are commonly used for electrical ship applications. To fulfill these requirements, an energy management subsystem (EMS) with a specific control algorithm must connect ESDs to the dc link of the motor drive system. In this research, the real-time simulation of shipboard power system (SPS), bidirectional DC-DC converter, EMS, and ESDs are designed, implemented, and controlled on OPAL-RT system to test SPS survivability and ESD performance in various speed operations.
Keywords: Real-time; Shipboard Power System; Energy Storage Devices; Power Management System; Li-iron Battery; Electrical Engineering (0544); Energy (0791); Engineering (0537)